The Geology of Kuwait - Abd el-aal, Abd el-aziz Khairy; Al-Awadhi, Jasem Mohammed; Al-Dousari, Ali (Regional Geology Reviews,, 2023)
This open access book contains a set of chapters covering all aspects of geosciences related to Kuwait and adjactent regions, including Iran, Saudi Arabia and the Arab Gulf states. It covers basic information about the geology including a wide range of geoscientific disciplines such as marine geology, structural geology, hydrogeology and geophysics related to the region. This book is aimed at researchers and students, as well as professionals in the field of hazard mitigation and petroleum exploration.